PENERAPAN MODEL PEMBELAJARAN KOOPERATIF COURSE REVIEW HORAY UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 4 PEKANBARU - Petrianis '; Maria Erna Erna; Elva Yasmi Amran Yasmi Amran (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was carried out by implementing the cooperative learning model Course Review Horay in order to increase student achievement the subject colloid in class XI IPA SMA Negeri 4 Pekanbaru. The type of this research is experimental research with pretest-postest design. The sample consists of two classes. They are class XI Science 1 as an experimental class and class XI Science 4 as a control class which were decided randomly after doing normality and homogenity test. Experimental class is a class that is applied cooperative learning model Course Review Horay, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 1,70> 1,67, means that the application of cooperative learning model Course Review Horay can improve student achievement on the subject of colloid class XI IPA SMA Negeri 4 Pekanbaru, increase learning of 4,32%. Keywords: Cooperative Learning, Course Review Horay